Self-efficacy, academic motivation, self-regulated learning and academic achievement - Mehmed Alafgani; Eny Purwandari (Program Studi bimbingan Konseling PPs UNM Makassar, 2019)
This study aims to empirically prove that the relationship between self-efficacy, academic motivation, self-regulated learning and academic achievement. In addition, empirically proved the mediating role of self-regulated learning on self-efficacy, academic motivation and student achievement. This study used quantitative expansive method. The sample of this study was 246 students of an Islamic senior high school recruited using census technique; thus, the entire population was used as the sample of the study. Data were collected using a questionnaire and were analyzed using Structural Equation Model (SEM). The results empirically show that there is a relationship between self-efficacy, academic motivation, self-regulated learning and academic achievement. However, there is no relationship between self-regulated learning and academic achievement.